Silent Tuberculous Endometritis Leading to Primary Amenorrhea in a Young Woman: A Case Report from A Tuberculosis Endemic Country - Hamurajib, Kuky Cahya; Alma, Nurulita Ainun; Tan, Giovanna Renee; Hanifah, Ifatul; Lutfi, Muhammad (Ethiopian Journal of Reproductive Health, 2025)
Background: We present the rare case of a 20-year-old patient with an asymptomatic tuberculous (TB) endometritis presenting with primary amenorrhea. Case presentation: The patient presented with absence of menstruation since birth. She had a history of TB treatment when she was 12 years old. She denied symptoms of lower abdominal pain, vaginal discharge, hirsutism, or significant systemic symptoms. The patient denied taking any diet plans nor medications. The patient had been prescribed hormonal combination therapy for 3 months, with no results. On clinical examination, secondary sexual development was appropriate for age. Laboratory examination revealed normal thyroid profiles, normal FSH, LH, estrogen, and prolactin profiles, as well as normal 46, XX karyotype. MRI examination revealed hypoplastic uterus and intraluminal lesions along the uterine cavity. Uterine synechiae and minimal hematometra was suspected. Hysteroscopy and laparoscopy were performed, revealing extensive uterine synechiae and significant intra-abdominal adhesions. Given the patient’s history of pulmonary and extrapulmonary TB, Interferon gamma release assay (IGRA) test was conducted and the result was positive. Conclusion: This case highlights the rare occurrence of tuberculosis-related uterine synechiae leading to primary amenorrhea, emphasizing the importance of considering tuberculosis in the differential diagnosis of unexplained primary amenorrhea in TB endemic regions. Keywords: Tuberculous endometritis, amenorrhea, uterine synechiae.